Effect of recombinant growth hormone on growth and survival rate of river catfish (Hemibagrus nemurus) in aquaponic system - Santi Ramayani; Iskandar Putra; Mulyadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted to determine the dose of recombinant growthhormone (rGH) of Ephinepelus lanceolatus supplemented in the commercial diet thatgenerates the best performance on body weight, body length, specific growth rate,survival rate, feed efficiency, and feed convertion rate of river catfish (Hemibagrusnemurus) in aquaponic system using leafy vegetable (Ipomea reptans). The dose ofrGH administrated was 3, 6, and 9 mg/kg of commercial feed and no rGHsupplementation as control. Each treatment was design in triplicates. Catfishes ataverage 5-7 cm were reared in a fiber tank in a density 23 fish/tank for 30 days. Thefish were fed with the rGH suplplemented diet once a three days at satiation. Theresults showed that growth body weight (4,84 g) and length (3,4 cm), feed efficiency(94.76%) of fish treated by rGH with the doses of 3 mg/kg feed was higher (P<0.05)than other treatment. Specific growth rate of 3 mg/kg feed was 3,69 %, higher thanother treatment. Feed convertion rate of rGH 3mg/kg feed (1.06) was lower than othertreatment. Thus, supplementation rGH 3 mg/kg feed of catfish once in three days canbe applied in enhance the growth catfish (Hemibagrus nemurus) with a bestperformance of growth.Keyword: river catfish, recombinant growth hormone, aquaponic